Differential expression of putative clotting protein gene in Vibrio Parahaemolyticus challenged giant fresh-water prawn, Macrobrachium Rosenbergii / Nazanin Ashgari Ziba - Ziba, Nazanin Ashgari (2014)
The growth of the freshwater prawn industry has not reached its great heights compared to the marine shrimps because of agriculturists’ innate fear of disease that will hamper the growth of the industry. High concentrations of infectious microorganisms (yeast, viruses and bacteria) in crustaceans during hot and cool seasons have resulted in a huge decline in prawn farming. Vibriosis, early mortality syndrome (EMS) and gastroenteritis due to zoonotic outbreaks have been a major threat to the rapid expanding production of freshwater prawns. The innate immune defense which leads to a lot of possible solutions needs to be thoroughly investigated for in-depth understanding of the defense mechanism of these prawns. This thesis investigates one of them namely the coagulation cascade which is a key mechanism in the invertebrate immune defense for avoiding loss of hemolymph particularly the clotting protein which activates a concatenate enzymatic reaction with the proPO system which leads to the production of the black-brownish pigments called melanin. In the current study, the putative clotting protein gene (CP gene) was sequenced from the fresh-water prawn transcriptome unigenes using Illumina’s Solexa sequencing technology. The putative clotting protein gene consisted of 5609 base pair with an open reading frame (ORF) length of 5139 bp. Putative CP encoded polypeptide has an estimated molecular mass of 189.9 k Da and 1712 amino acids with a predicted isoelectric point of 5.44. The deduced amino acid sequences of the clotting protein gene were aligned with other CP family members indicating the highest sequence similarity with A7YIH6 (Penaeus japonicus clottable protein) , B5KMA2 (Penaeus monodon clottable protein) , Q9U572 (Penaeus monodon hemolymph clottable protein), A8DR94 (Litopenaeus vannamei hemolymph clottable protein) and Q9UAR3 (Pacifastacus leniusculus clotting protein). DNAstar protein analysis showed that M. rosenbergii CP is a protein with a hydrophilic structure and good antigenicity index. Analysis using PROSITE to identify the domains on the CP protein showed that positions 81 to 782 corresponds to the vitellogenin domain and positions from 1439 to 1635 correspond to the VWFD domain. Neibor–Joining phylogenetic tree of Clotting protein based on the vitellogenin domain of organism group ranging from invertebrate to vertebrate constructed on the basis of Poisson model and built at a boot strap of 1000. The tree represents tr_Q9UAR3 (Pacifastacus leniusculus clotting protein) as the closest ancestral protein. The results of the relative real-time PCR analysis clearly showed that CP expression occurs predominantly in most tissues of Macrobrachium rosenbergii but with remarkably highest expression in stomach followed by in pleopods. According to the outcome of the gene expression analysis, the mRNA transcription of the clotting protein gene in Vibrio parahaemolyticus challenged Macrobrachium rosenbergii was significantly induced in the stomach. The overall results of the current study indicate that the CP is without doubt an essential immune gene involved in the immune response against V. parahaemolyticus infection in Macrobrachium rosenbergii.